A striking response of plasmablastic lymphoma of the oral cavity to bortezomib: a case report. Issue 1 (December 2015) - Hirosawa, Makoto; Morimoto, Hiroaki; Shibuya, Ryo; Shimajiri, Shohei; Tsukada, Junichi
Abstract Background Plasmablastic lymphoma (PBL) is a rare and aggressive subtype of non-Hodgkin diffuse large B-cell lymphoma originally with a predilection to the oral cavity of patients infected with HIV. However, PBL of extraoral sites possesses clinicopathological characteristics distinct from oral PBL. Recently, therapeutic approaches using a proteasome inhibitor bortezomib to PBL of extraoral sites have been reported. We present a PBL patient with a bulky tumor of the oral cavity, who dramatically responded to bortezomib. Case Presentation The patient was a 58 year-old Japanese male, who presented with a rapidly progressive history of a swelling on his left cheek and restricted mouth opening. He did not have a history or evidence of immunosuppression including HIV infection. A computed tomography demonstrated a bulky tumor in the oral cavity without enlarged lymph nodes. The tumor showed the proliferation of large lymphoid cells with centroblastic morphology, which were positive for CD138, CD38, CD56 and MUM-1, and negative for CD20, CD79a, BCL-6 and HHV8. The Ki-67 proliferation index was almost 100 %. Neither osteolytic lesions nor M-protein was observed. One week after the initiation of bortezomib, a marked regression of the oral tumor was obtained. Conclusions Thus, our case demonstrated the effectiveness of bortezomib on PBL of the oral cavity as well as the extraoral sites.